Elevated circulating cell-free mitochondrial DNA in fabry disease: insights into inflammatory activation - Yuan, Yujing; Zhang, Xinyu; Zhao, Yawen; Wang, Yikang; Huang, Jingyi; Wang, Qingqing; Song, Xueqin; Deng, Jianwen; Wang, Zhaoxia; Yuan, Yun; Zhang, Wei (Frontiers in Immunology, 2026)
ObjectiveThis study aimed to investigate mitochondrial dysfunction and its role in the pathogenesis of Fabry disease (FD) by analyzing circulating cell-free DNA (ccf-DNA) in patients with FD.MethodsSixty-six FD patients and 21 healthy controls (ctrls) were enrolled. Levels of plasma mitochondrial- (ccf-mtDNA) and nuclear-derived ccf-DNA (ccf-nDNA) were quantified by quantitative reverse-transcription PCR (RT-qPCR), and 14 inflammatory cytokines were measured in treatment-naïve patients. Associations among ccf-DNA levels, cytokine profiles, disease biomarkers, and clinical markers were analyzed, with subgroup analyses stratified by sex, genotype, clinical subtype, and disease severity.ResultsTreatment-naïve patients exhibited significantly higher ccf-mtDNA (z=–4.530, P-adj<0.001) and mtDNA/nDNA ratio (z=–2.613, P-adj=0.014) compared with ctrls. In the long-term enzyme replacement therapy (ERT) group (> 12 months), ccf-mtDNA copy number remained elevated (z=–3.141, P-adj=0.006), whereas the mtDNA/nDNA ratio did not differ significantly (z=–1.013, P-adj=0.311). No differences in ccf-nDNA were observed between treatment-naïve patients or the long-term ERT group compared with ctrls. Receiver operating characteristic analysis demonstrated the strong diagnostic performance of ccf-mtDNA (area under the curve=0.860), with 70% sensitivity and 91% specificity at an optimal cut-off value of 1,793,188.04 copies. Both ccf-mtDNA and mtDNA/nDNA ratio correlated positively with inflammatory cytokines including interleukin-17F and tumor necrosis factor-β, with stronger associations observed in male patients with classic FD. No correlations were observed with disease duration, α-galactosidase A activity, plasma globotriaosylsphingosine or clinical markers after adjustment for age and sex. Similarly, ccf-DNA measures did not differ significantly by sex, GLA mutation type (truncated vs. non-truncated), FD subtype (classic vs. non-classic), or across subgroups defined by disease severity or organ involvement (high vs. low MSSI, with or without hypertrophic cardiomyopathy, with or without chronic kidney disease, mild vs. severe white matter lesions, with or without neuralgia, or mild vs. severe pain).ConclusionsMitochondrial dysfunction, reflected by elevated ccf-mtDNA, is implicated in FD pathogenesis and may be linked to inflammatory activation. ccf-mtDNA represents a promising diagnostic biomarker for FD, potentially offering an additional therapeutic target when combined with ERT.